PERUBAHAN SOSIAL-EKONOMI NELAYAN KERAMBA DI SAMOSIR (1990-2015) - Novita Margaretha Pandiangan; Ihut Marasi Pakpahan; Pristi Suhendro Lukitoyo; Syarifah Syarifah (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
This study will discuss the changes that occurred in the social and economic sectors of cage fishermen in Samosir Regency from 1990-2015. This study aims to determine and analyze the development of cage fishermen's lives in the social and economic fields. The methods used in this research are quantitative and qualitative methods. Data were collected through interviews, literature study and observation. The people of Samosir have depended on Lake Toba for their lives, especially for people who live in coastal areas. This vast lake has provided a big change for fishermen in developing their socio-economic life. Fishermen carry out fish farming activities using floating net cages in Lake Toba to fulfill all aspects of their life needs. through the cultivation of floating net cage fish, the economic growth of the community is increasing and the social conditions of the family are getting more prosperous.